Dietary 25-hydroxycholecalciferol modulates gut microbiota and improves the growth, meat quality, and antioxidant status of growing-finishing pigs - Zhang, Lianhua; Long, Shenfei; Wang, Hongliang; Piao, Xiangshu (Frontiers in Microbiology, 2023)
Introduction 25-Hydroxycholecalciferol (25OHD3) is the active metabolite of regular vitamin D3in vivo, which has a stronger biological activity and is more easily absorbed by the intestine than regular vitamin D3. Our study aimed to detect the potential influences of 25OHD3 on pork quality, antioxidant status, and intestinal microbiota of growing-finishing pigs receiving low-phosphorus (P) diet. Methods and results Forty pigs [initial body weight (BW): 49.42 ± 4.01 kg] were allocated into two groups including low-P diet (CON group) and low-P diet supplemented with 50 μg/kg 25OHD3 (25OHD3 group). The whole experiment lasted for 88 days, including phase 1 (day 1–28), phase 2 (day 29–60), and phase 3 (day 61–88). The results showed that 25OHD3 supplementation tended to decrease feed conversion ratio in phase 3 and overall phase in comparison with the CON group. 25OHD3 increased (p < 0.05) serum contents of superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px), and decreased (p < 0.05) serum bone-specific alkaline phosphatase level. 25OHD3 increased (p < 0.05) mucosal GSH-Px activity in the duodenum and ileum, and tended to increase redness value and the activities of total antioxidant capacity and SOD in longissimus dorsi. 25OHD3 significantly upregulated the mRNA level of copper/zinc superoxide dismutase, and tended to change the mRNA levels of nuclear factor E2-related factor 2 and kelch-like ECH-associated protein 1 in longissimus dorsi. Moreover, 25OHD3 supplementation decreased (p < 0.05) n-6/n-3 and iodine value in longissimus dorsi. For bone quality, 25OHD3 supplementation increased (p < 0.05) calcium content, bone mineral content, and breaking strength in the metacarpal bones. Moreover, the colonic abundance of Lactobacillus was significantly higher in pigs fed with 25OHD3, and exhibited a positive association with serum antioxidant status, pork quality, and bone characteristics. Conclusion Overall, the inclusion of 25OHD3 in low P diet partly improved production performance, meat quality, antioxidant capacity, bone properties, and gut microbiota composition of growing-finishing pigs.